1996
DOI: 10.1007/bf02637073
|View full text |Cite
|
Sign up to set email alerts
|

Increased docosahexaenoic acid levels in human newborn infants by administration of sardines and fish oil during pregnancy

Abstract: In rhesus monkeys, maternal n-3 fatty acid deficiency during pregnancy produces infant monkeys deficient in n-3 fatty acids at birth. These results stimulated current experiments to find out if n-3 fatty acids from fish in the diets of pregnant women would influence the concentration of docosahexaenoic acid (DHA, 22:6 n-3) in the newborn human infant. Fifteen healthy pregnant women were enrolled to receive a 9-wk dietary supplementation of n-3 fatty acids from the 26th to the 35th wk of pregnancy. Sixteen preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 12 publications
5
61
1
2
Order By: Relevance
“…On balance, results from our observational study and those of others (10,(24)(25)(26)(27), are consistent with intervention studies (28)(29)(30) that have documented increased omega-3 fatty acids in maternal plasma and/or erythrocyte after omega-3 fatty acid supplementation during pregnancy. We could find no published reports of maternal habitual fish consumption and plasma lipid and lipoprotein concentrations in early pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…On balance, results from our observational study and those of others (10,(24)(25)(26)(27), are consistent with intervention studies (28)(29)(30) that have documented increased omega-3 fatty acids in maternal plasma and/or erythrocyte after omega-3 fatty acid supplementation during pregnancy. We could find no published reports of maternal habitual fish consumption and plasma lipid and lipoprotein concentrations in early pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…The converse is that enhancing DHA status during pregnancy could potentially benefit the fetus by providing an abundant source for brain development. Connor et al (1996) reported that pregnant women who regularly consumed sardines or fish oil increased their plasma DHA levels and transferred additional DHA and other n-3 fatty acids to their fetuses. In a randomised, double-blind intervention trial, Montgomery et al (2003) supplemented pregnant women with either DHA (200 mg/d) or oleic acid.…”
Section: Infant Developmentmentioning
confidence: 99%
“…The relative importance of diet and adipose stores to overall trans-placental LCPUFA flux may be inferred from feeding studies, which show that supplementation at the level of 100 mg/day of DHA or 336 mg/day of fish oils (Velzing-Aarts et al, 2001) has no measurable effect on cord blood n-3 concentrations. There are reports of measurable effects on cord blood of supplementation with marine oils but at much higher levels: 2600 mg/day (Connor et al, 1996) and 2700 mg/day of n-3 fatty acids and it appears that intakes of 500-1000 mg/day (3-5 times the normal dietary intake) are necessary before an increase in the n-3 content of the cord can be achieved with late pregnancy supplementation (Velzing-Aarts et al, 2001). Contrast this with the observation that fairly modest differences between individuals in the n-3 content of their normal diet can have significant effects on the cord blood composition (Otto et al, 1997).…”
Section: Implications For Dietary Recommendationsmentioning
confidence: 99%